Finding the Roots of (x+3)(x2)(x+1)(x1) = 0
This equation is already factored, making it easy to find the roots. Here's how:
Understanding the Concept
The roots of an equation are the values of x that make the equation true. In this case, we are looking for the values of x that make the entire product equal to zero.
The Zero Product Property
The Zero Product Property states that if the product of two or more factors is zero, then at least one of the factors must be zero.
Applying the Property
Since we have four factors in the equation, we can set each factor equal to zero and solve for x:

x + 3 = 0
Solving for x, we get x = 3 
x  2 = 0 Solving for x, we get x = 2

x + 1 = 0 Solving for x, we get x = 1

x  1 = 0 Solving for x, we get x = 1
The Roots
Therefore, the roots of the equation (x+3)(x2)(x+1)(x1) = 0 are x = 3, x = 2, x = 1, and x = 1.
Conclusion
By applying the Zero Product Property, we were able to easily find the roots of the equation. Each root represents a value of x that makes the equation true.